2013
DOI: 10.1111/sdi.12147
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous and Surgical Insertion of Peritoneal Catheter in Patients Starting in Chronic Dialysis Therapy: A Comparative Study

Abstract: Percutaneous peritoneal catheter insertion can be performed by trained nephrologists. The objective of this study was to compare the outcome of peritoneal dialysis (PD) catheters percutaneous inserted with the traditional surgical technique. One hundred twenty-one PD catheters were placed in 121 stage-5 Chronic kidney disease patients using three techniques: percutaneous insertion (Group P, n = 53), percutaneous insertion guided by radioscopy (Group R, n = 26), and surgical insertion (Group S, n = 42). The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…Moreover, the conventional Seldinger technique uses a blind puncture process, so it is difficult to place the catheter accurately and there is risk of organ injury and hemorrhage. Some studies have even found no advantages of percutaneous catheterization over traditional open surgery or laparoscopic surgery regarding catheter‐related complications and catheter survival duration, 12‐15 suggesting the need for further improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the conventional Seldinger technique uses a blind puncture process, so it is difficult to place the catheter accurately and there is risk of organ injury and hemorrhage. Some studies have even found no advantages of percutaneous catheterization over traditional open surgery or laparoscopic surgery regarding catheter‐related complications and catheter survival duration, 12‐15 suggesting the need for further improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Medani et al reported a 90% success rate, defined as maintenance of normal catheter function for 2‐4 weeks, using the blind Seldinger technique in patients receiving catheterization for the first time without a history of abdominal surgery, similar to that of a parallel surgical placement group 16 . However, van Laanen et al reported that only 77% of patients maintained normal catheter function for 2 weeks after surgical insertion (failure rate of 23%), 11 and several other randomized control trials have also reported relatively high (16% to 30%) failure rates for catheterization by surgical laparotomy 12‐14 . Thus, all the previous techniques show substantially greater failure rates (up to 30%) than ultrasound‐guided percutaneous peritoneal dialysis catheter placement using a multifunctional bladder paracentesis trocar (around 4% failure).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the success rate is similar to that of surgicallyinserted PD catheters. [27][28][29] Supine intermittent PD can be immediately started after PD catheter insertion, avoiding temporary HD.…”
Section: Peritoneal Dialysis: Who?mentioning
confidence: 99%
“…After the initial reports of two perforation complications by blind trocar technique in 1991, presumably due to adhesions, standard practice was to exclude patients with complex abdomen from all percutaneous techniques (16). Since 2000, only one study by Chula et al reported patients undergoing percutaneous placement with complex abdomen (21% of patients) (17).…”
mentioning
confidence: 99%